PENDEKATAN-PENDEKATAN DALAM EVALUASI HASIL BELAJAR DI TINGKAT PENDIDIKAN DASAR - Rahayu Rahmadani; Ira Maya Sofa; Nova Arianti; Ratna Juita; Rahma Yuni; Hafiz Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Evaluation of learning outcomes at the basic education level faces challenges in implementing an assessment system that not only measures cognitive aspects, but also covers the development of competencies as a whole. This research aims to examine various learning outcome evaluation approaches that are relevant and effective in primary schools. The method used is a literature study with a qualitative approach and content analysis of theoretical and practical sources related to learning evaluation. The results show that approaches such as formative, summative, authentic, portfolio, as well as self- and peer-assessment have an important role in supporting competency-based learning and maximum development of learners' potential. The implementation of these approaches still faces obstacles in the field, such as limited teacher capacity and lack of operational guidelines.